2021
DOI: 10.1111/jac.12538
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen stress inhibits root growth by regulating cell wall and hormone changes in cotton (Gossypium hirsutum L.)

Abstract: Roots play an important role in the response to nitrogen stress in cotton. To better understand the molecular and physiological mechanisms underlying the adaptation of cotton roots to nitrogen stress, the responses of genes in roots to nitrogen changes were analysed by RNA sequencing (RNA-seq), and morphological and physiological indicators were measured for verification. This study revealed that lack of nitrogen stress (LN, 0 mm) and excess nitrogen stress (HN, 8 mm) inhibited root growth.Moderate nitrogen (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…This study also revealed that under the condition of excessive nitrogen supply, exogenous melatonin was also beneficial to prevent the excessive accumulation of ammonium ions in mesophyll and root cells. Due to excessive nitrogen supply, plant development was significantly inhibited, mainly in the root (Chen et al 2021). Therefore, in this study, it was observed that the expression of key genes about nitrogen metabolism was alleviated in melatonin treatment, and the upregulation effect was more evident in the root.…”
Section: Discussionmentioning
confidence: 67%
“…This study also revealed that under the condition of excessive nitrogen supply, exogenous melatonin was also beneficial to prevent the excessive accumulation of ammonium ions in mesophyll and root cells. Due to excessive nitrogen supply, plant development was significantly inhibited, mainly in the root (Chen et al 2021). Therefore, in this study, it was observed that the expression of key genes about nitrogen metabolism was alleviated in melatonin treatment, and the upregulation effect was more evident in the root.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, Hou et al (2021) recorded the highest nitrogen accumulation in cotton when N was applied at 223.88 and 242.77 kg ha −1 . However, excessive application of N causes soil and environmental pollution, degrading soil biological activities, nutrient imbalance, impairs growth, and ultimately crop productivity in terms of reduced yield and NUE ( Ju et al, 2009 ; Liu et al, 2013 ; Chen et al, 2021 ). According to Macdonald et al (2016) , a high dose of N also causes leaching and runoff losses owing to reducing the availability of N in the rhizosphere.…”
Section: N Accumulation In Cotton: Factors Affecting N Accumulationmentioning
confidence: 99%
“…According to Macdonald et al (2016) , a high dose of N also causes leaching and runoff losses owing to reducing the availability of N in the rhizosphere. In addition, a deficiency of N reduced root growth ( Chen et al, 2021 ). The root system in cotton directly influences the N use efficiency, which can be increased by regulating the root system ( Chen et al, 2018 , 2021 ).…”
Section: N Accumulation In Cotton: Factors Affecting N Accumulationmentioning
confidence: 99%
See 2 more Smart Citations